Reentrant Spin Glass and Large Coercive Field Observed in a Spin Integer Dimerized Honeycomb Lattice. (28th September 2020) - Zhai, Yuan‐Qi; Deng, Yi‐Fei; Fu, Zhendong; Feng, Erxi; Su, Yixi; Shiga, Takuya; Oshio, Hiroki; Zheng, Yan‐Zhen
Abstract: 2D magnetic materials with dimerized honeycomb lattices can be treated as mixed‐spin square lattices, in which a quantum phase transition may occur to realize the Bose–Einstein condensation of magnons under reachable experimental conditions. However, this has never been successfully realized with integer spin centers. Herein, a spin integer ( S = 2) dimerized honeycomb lattice in an iron(II)‐azido compound [Fe(4‐etpy)2 (N3 )2 ] n (FEN, 4‐etpy = 4‐ethylpyridine) is realized. Morphology characterization by transmission electron microscopy, scanning electron microscopy, and atomic force microscopy spectroscopies show that the thinnest place of the sample is ≈13 nm, which is equal to ten layers of the compound. In contrast to the common magnetic properties of long‐range magnetic ordering, Mössbauer and polarized neutron scattering studies reveal that FEN exhibits a reentrant spin glass behavior owing to competing ferro‐ and antiferromagnetic exchange‐coupling interactions within the lattice. Two spin glass phases with disparate canting angles are characterized at 39 and 28 K, respectively. By using Curély's model, two exchange‐coupling constants ( J 1 = +35.8 cm −1 and J 2 = −3.7 cm −1 ) can be simulated. Moreover, a very large coercive field of ≈1.9 Tesla is observed at 2 K, making FEN a "very hard" van der Waals 2D magnetic material. Abstract : A dimerized honeycomb lattice with integer spins is realized in an iron(II)‐azido compound. Morphology characterization shows that the thinnest place of the sample is ≈13 nm, which comprises ten layers of the compound. Magnetic, Mössbauer, and polarized neutron scattering studies reveal a reentrant spin glass behavior, which leads to a "very hard" magnetic hysteresis loop at lower temperatures.